2020
DOI: 10.3390/antiox9040342
|View full text |Cite
|
Sign up to set email alerts
|

Pure Trans-Resveratrol Nanoparticles Prepared by a Supercritical Antisolvent Process Using Alcohol and Dichloromethane Mixtures: Effect of Particle Size on Dissolution and Bioavailability in Rats

Abstract: The aim of this study was to prepare pure trans-resveratrol nanoparticles without additives (surfactants, polymers, and sugars) using a supercritical antisolvent (SAS) process with alcohol (methanol or ethanol) and dichloromethane mixtures. In addition, in order to investigate the effect of particle size on the dissolution and oral bioavailability of the trans-resveratrol, two microparticles with different sizes (1.94 µm and 18.75 µm) were prepared using two different milling processes, and compared to trans-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
(54 reference statements)
2
25
0
Order By: Relevance
“…In fact, the AUC 0→8 h and C max values of trans -resveratrol increased with the increasing degree and duration of in vitro supersaturation. This tendency is similar to that of trans -resveratrol-loaded composite nanoparticles previously reported [ 20 , 21 ]. Furthermore, the absolute oral bioavailability (F%) of trans -resveratrol was estimated to be 40% for the Eudragit E/HCl solid dispersion (10/90).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, the AUC 0→8 h and C max values of trans -resveratrol increased with the increasing degree and duration of in vitro supersaturation. This tendency is similar to that of trans -resveratrol-loaded composite nanoparticles previously reported [ 20 , 21 ]. Furthermore, the absolute oral bioavailability (F%) of trans -resveratrol was estimated to be 40% for the Eudragit E/HCl solid dispersion (10/90).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the absolute oral bioavailability (F%) of trans -resveratrol was estimated by dividing the AUC 0→8 h value obtained from oral administration by the AUC 0→8 h value obtained from intravenous administration with dose normalization. The AUC 0→8 h value of trans -resveratrol after intravenous administration used was from our previous study [ 20 ]. As shown in Figure 5 , the oral absorption of trans -resveratrol was significantly enhanced by the Eudragit E/HCl solid dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles and nanocrystals containing APIs can be obtained with different techniques, such as spray-drying, freeze-drying, coacervation, jet-milling, and solvent evaporation [21][22][23][24][25][26][27]. However, toxic organic solvents are widely used in these traditional processes; high temperatures and long postprocess treatments are also employed to remove liquid solvents from the particles/crystals produced.…”
Section: Introductionmentioning
confidence: 99%
“…High process temperatures can cause possible degradation of the active compound, in addition to the fact that the removal of the solvent from the final product is often not complete. Moreover, traditional micronization/nanonization techniques usually lead to the achievement of products characterized by irregular morphology and broad PSDs [21][22][23][24]. Many literature studies have demonstrated the possibility of overcoming all these drawbacks by using supercritical carbon dioxide (scCO 2 ) for the drug micronization/nanonization [21][22][23][24][28][29][30].…”
Section: Introductionmentioning
confidence: 99%